Transmission of Carbapenem-Resistant Klebsiella pneumoniae in US Hospitals. (29th September 2022) - Luterbach, Courtney L; Chen, Liang; Komarow, Lauren; Ostrowsky, Belinda; Kaye, Keith S; Hanson, Blake; Arias, Cesar A; Desai, Samit; Gallagher, Jason C; Novick, Elizabeth; Pagkalinawan, Stephen; Lautenbach, Ebbing; et al.
Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae (CR Kp ) is the most prevalent carbapenem-resistant Enterobacterales in the United States. We evaluated CR Kp clustering in patients in US hospitals. Methods: From April 2016 to August 2017, 350 patients with clonal group 258 CR Kp were enrolled in the Consortium on Resistance Against Carbapenems in Klebsiella and other Enterobacteriaceae, a prospective, multicenter, cohort study. A maximum likelihood tree was constructed using RAxML. Static clusters shared ≤21 single-nucleotide polymorphisms (SNP) and a most recent common ancestor. Dynamic clusters incorporated SNP distance, culture timing, and rates of SNP accumulation and transmission using the R program TransCluster. Results: Most patients were admitted from home (n = 150, 43%) or long-term care facilities (n = 115, 33%). Urine (n = 149, 43%) was the most common isolation site. Overall, 55 static and 47 dynamics clusters were identified involving 210 of 350 (60%) and 194 of 350 (55%) patients, respectively. Approximately half of static clusters were identical to dynamic clusters. Static clusters consisted of 33 (60%) intrasystem and 22 (40%) intersystem clusters. Dynamic clusters consisted of 32 (68%) intrasystem and 15 (32%) intersystem clusters and had fewer SNP differences than static clusters (8 vs 9; P = .045; 95% confidence interval [CI]: −4 to 0). Dynamic intersystem clusters contained more patients than dynamic intrasystem clusters (median [interquartile range], 4 [2, 7] vs 2 [2, 2]; P = .007; 95% CI: −3 to 0). Conclusions: Widespread intrasystem and intersystem transmission of CR Kp was identified in hospitalized US patients. Use of different methods for assessing genetic similarity resulted in only minor differences in interpretation. Abstract : We characterized clusters of carbapenem-resistant Klebsiella pneumoniae among patients in US hospitals using static and dynamic methodologies of clustering. Widespread intrasystem and intersystem transmission was identified. Use of different methods to assess clustering resulted in only minor differences in interpretation.